The Implementation of Front Office SOP Based on CHSE during the Covid-19 Pandemic - Made Raras Ari Udhyani; Ni Nyoman Sri Astuti; I Gusti Agung Mas Krisna Komala Sari; Made Sudiarta (International Journal of Glocal Tourism, 2022)
Purpose: This research is to analyze the implementation of standard operating procedures (SOP) in the front office department during the Covid-19 pandemic due to the use of Cleanliness, Health, Safety, and Environment Sustainability (CHSE) health protocol which is expected to reduce the spread of the virus. Research methods: This research was conducted at Wyndham Garden Kuta Beach Bali using observation data collection methods, interviews and literature study. Participants of this research were front office managers, front office supervisors, the CHSE team and several guests from Wyndham Garden Kuta Beach Bali. The data analysis technique used is descriptive qualitative method. Findings: The implementation of standard operating procedures carried out by the front office department of Wyndham Garden Kuta Beach Bali has been carried out in accordance with the CHSE-based health protocol which has a good impact on guests, including increasing guests' trust in the hotel. Implications: As for the hotel, it is an asset to attract guests to stay during the pandemic so that it keeps hotel operations running.